Rate of hourly change in serum beta-human chorionic gonadotropin levels in ectopic pregnancy can predict the success of treatment with single-dose methotrexate: A retrospective observational study. (October 2021) - Lavie, G.; Kais, M.; Tendler, R.; Marwan, O.; Bornstein, J.; Sharon, A.
Abstract: Objective: To determine whether the success of treatment with single-dose methotrexate (SD MTX) for ectopic pregnancy can be predicted using the rate of change in serum β-human chorionic gonadotropin (β-hCG) level. Study design: This was a retrospective observational study conducted at a tertiary referral centre. The study population included women who underwent treatment with SD-MTX for ectopic pregnancy. We analysed data of 119 women treated with SD-MTX for ectopic pregnancy at the Galilee Medical Centre between 2012 and 2016. Success was defined as a <15% decrease in β-hCG level between days 4 and 7, with no need for a second dose of MTX or surgical intervention. The dynamics of serum β-hCG levels before treatment were considered as the main outcomes. Results: SD-MTX administration was successful in 77 (65%) patients. The average baseline β-hCG level was significantly lower in women with successful outcomes than in those without successful outcomes (763.1 vs. 1429.63 mIU/L, respectively, p  < 0.0048). The hourly change in β-hCG level was significantly lower in those with successful outcomes than in those without successful outcomes (0.38 vs. 5.73 mIU/mL, respectively, p  < 0.0023). The percentage change in β-hCG level was 13.1%, which was not significantly different between the groups ( p  < 0.133). At serum β-hCG level < 946 mIU/mL and sac size < 2.55 cm, the treatment was successful in 88% of women. Conclusions: We propose a predictive model of hourly change in β-hCG to achieve successful treatment using SD-MTX in ectopic pregnancy based on objective and measurable criteria.